2004
DOI: 10.1037/0021-9010.89.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Data Quality Affects Meta-Analytic Conclusions: A Response to Miner and Raju (2004) Concerning Entrepreneurial Risk Propensity.

Abstract: J. B. Miner and N. S. Raju (2004) contended that there are additional studies that compare the risk propensity of entrepreneurs and managers, which, when added to the data from W. H. Stewart and P. L. Roth (2001) and meta-analyzed, produce relationships between risk propensity and entrepreneurial status that are substantially weaker than previously believed. This conclusion was evaluated by identifying and examining methodological problems associated with their inclusion of effect sizes (i.e., ds) from studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 54 publications
(112 reference statements)
3
74
1
Order By: Relevance
“…This cumulative evidence speaks to the ongoing debate in psychology on the risk-propensity of entrepreneurs. Note for example two recent meta-analytical studies that point in contrasting directions on this debate (Miner and Raju, 2004;Stewart and Roth, 2004). Another important literature we hope the cumulation of the three studies on entrepreneurial expertise speak to is the one on behavioral decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…This cumulative evidence speaks to the ongoing debate in psychology on the risk-propensity of entrepreneurs. Note for example two recent meta-analytical studies that point in contrasting directions on this debate (Miner and Raju, 2004;Stewart and Roth, 2004). Another important literature we hope the cumulation of the three studies on entrepreneurial expertise speak to is the one on behavioral decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies are business opportunities for Abbreviations: K, number of studies; N, total number of observations; r, mean correlation; r c , reliability-corrected and sample-size weighted mean correlation; r w , sample-size weighted mean correlation. b There was an exchange between Miner & Raju (2004) and Stewart & Roth (2001) that has been resolved by the meta-analysis by Stewart & Roth (2004).…”
Section: Entrepreneurial Alertnessmentioning
confidence: 99%
“…Furthermore, previous studies have indicated that entrepreneurs are highly motivated to achieve goals (Stewart & Roth, 2004;Wang & Liang, 2015). In other words, they exhibit high levels of conscientiousness.…”
Section: Personality Traitsmentioning
confidence: 99%